PENERAPAN MODEL PEMBELAJAN PROBLEM SOLVING UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR SISWA POKOK BAHASAN ENERGI SISWA KELAS IV SD ISLAM ROUDLOTUL QUR’AN MOJOKERTO - Isma Afifatussa’diyah; Singgih Baktiarso; Traspsilo Prihandono (JS (JURNAL SEKOLAH), 2022)
Abstract :  The Application Of The Learning Model To Improve Scientific Attitude And Learning Outcomes Of Students Of Class IV Energy Students Of Roudlotul Qur'an Islamic Elementary School, Mojokerto, The purpose of this classroom action research is to find out the improvement of scientific attitudes and student learning outcomes on the subject of energy after applying the Problem Solving Learning Model. This research uses classroom action research with two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The location of this classroom action research was carried out at the Islamic Elementary School Roudlotul Qur'an Mojokerto, East Java province. The research was carried out in December 2021. The subjects of this research were the fourth grade students of Islamic Elementary School Roudlotul Qur'an Mojokerto, totaling 23 students. The main topic of discussion is about the material "Energy". The data obtained from the implementation of the activities are interviews, observations, documentation, formative tests. From the results of the analysis, it was found that scientific attitudes and student learning outcomes experienced a good increase, namely from the implementation of pre-cycle activities to cycle II. The conclusion of this study is that the Problem Solving learning model can improve scientific attitudes and student learning outcomes and can have a positive effect on Islamic Elementary School students Roudlotul Qur'an Mojokerto, the Problem Solving learning model can be used as an effort to improve learning activities.Keywords: Learning Outcomes, Scientific Attitude, Problem Solving Abstrak : Penerapan Model Pembelajan Problem Solving untuk Meningkatkan Sikap Ilmiah Dan Hasil Belajar Siswa Pokok Bahasan Energi Siswa Kelas IV SD Islam Roudlotul Qur’an Mojokerto. Tujuan dari penelitian tindakan kelas ini yaitu untuk mengetahui peningkatan sikap ilmiah dan hasil belajar siswa pokok bahasan energi setelah diterapkan Model Pembelajaran Problem Solving. Penelitian ini menggunakan penelitian tindakan kelas dengan dua kali siklus. Setiap siklus terdiri dari empat tahap yaitu perencanaan,  pelaksanaan, pengamatan dan  refleksi. Lokasi penelitian tindakan kelas ini dilaksanakan di SD Islam Roudlotul Qur’an Mojokerto, provinsi Jawa Timur. Penelitian dilaksanakan pada Desember 2021. Subjek penelitian ini adalah siswa kelas IV SD Islam Roudlotul Qur’an Mojokerto yang berjumlah 23 siswa. Pokok bahasan yang disampaikan yaitu mengenai materi “Energi”. Data yang diperoleh dari pelaksanaan kegiatan yaitu wawancara, observasi, dokumentasi, tes formatif. Dari hasil analisis didapatkan sikap ilmiah dan hasil belajar siswa mengalami peningkatan yang baik, yaitu dari pelaksanaan kegiatan pra siklus hingga siklus II. Kesimpulan dari penelitian ini adalah model pembelajaran Problem Solving dapat meningkatkan sikap ilmiah dan hasil belajar siswa serta dapat berpengaruh positif terhadap siswa SD Islam Roudlotul Qur’an Mojokerto, model pembelajaran Problem Solving dapat dijadikan upaya perbaikan kegiatan pembelajaran.Kata Kunci: Hasil Belajar, Sikap Ilmiah, Problem Solving